Trends in wood biofuel production, marketing and utilization in Latvia - Ielejs, Klāvs (SLU/Southern Swedish Forest Research Centre, 2017)
Wood biofuel production and use of wood biofuel is an important part of the Latvian economy because it is an alternative to fossil energy sources. That encourage to the preservation of the environment and offers an opportunity to achieve the objectives set by the EU and Latvia in relation to the use of renewable energy production. The aim of thesis is to examine the literature on wood bioenergy production, marketing in Latvia. Wood biofuel producers and experts are questioned within their challenges and prospects in wood biofuel production and marketing in Latvia. Data were collected from 107 wood biofuel companies using interviews and were analyzed using SWOT and simple percentages. The results showed that almost 100% of the wood biofuel in Latvia are produced from local wood raw materials. Wood is the most important domestic household fuel in Latvia, and opportunities in biofuel domestic and export markets exist in the country. Latvia has great potential to increase its energy supply system using biofuel products and become less dependent on fossil fuel. Biofuel producers in Latvia face challenges such as shortage of raw materials, unstable market prices, and difficulties in accessing funds for investment as well as institutional rules and regulations. In order to achieve Latvian renewable energy policy goals an effective national policy is required to promote the use of renewable energy.